Risk Factors for the Incidence of the Volar Lunate Facet Fragments in Distal Radius Fractures - Mitsuzawa, Sadaki; Takeuchi, Hisataka; Tsukamoto, Yoshihiro; Yamashita, Shinnosuke; Ota, Satoshi; Onishi, Eijiro; Yasuda, Tadashi (Journal of Wrist Surgery, 2023)
Background The volar lip of the distal radius is the key structure for wrist joint stability. Rigid fixation of the volar lunate facet (VLF) fragment is difficult because of its unique anatomy, and a high rate of postoperative displacement was demonstrated.Purposes The aim of the study is to identify risk factors for VLF in distal radius fractures (DRFs) and to reconsider the important point for primary fixation.Patients and Methods One hundred fifty-five patients who underwent open reduction and internal fixation for an DRF were included and classified into one of the following two groups: VLF(+)or VLF(−). Demographic data, including age, sex, body mass index (BMI), laterality, trauma mechanism, and AO Foundation/Orthopaedic Trauma Association (AO/OTA) classification were recorded. Several parameters were investigated using wrist radiographs of the uninjured side and computed tomography scans of the injured side. Univariate and multivariate logistic regression analyses were performed to evaluate the risk factors for VLF.Results There were 25 patients in the VLF(+) group and 130 patients in the VLF(−) group. The incidence of VLF was 16.1%. The VLF(+) group tended to have a higher BMI and higher energy trauma mechanism. The odds ratio for the sigmoid notch angle (SNA), volar tilt (VT), and lunate facet curvature radius (LFCR) were 0.84, 1.32, and 0.70, respectively, with multivariate analysis, which was significant. A smaller SNA, larger VT, and smaller LFCR are potential risk factors for VLF.Conclusion Over-reduction of the VT at primary fixation should be avoided because it could place an excess burden on the VLF and cause subsequent postoperative fixation failure and volar carpal subluxation.Level of Evidence IV
Keywords: distal radius fracture; volar lunate facet fragment; loss of reduction; risk factor